2014
DOI: 10.1155/2014/413071
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive Crisis, Burden, Management, and Outcome at a Tertiary Care Center in Karachi

Abstract: Objectives. Hypertension, if uncontrolled, can lead to hypertensive crisis. We aim to determine the prevalence of hypertensive crisis, its management, and outcome in patients presenting to a tertiary care center in Karachi. Methods. This was a cross-sectional study conducted at the Aga Khan University, Karachi, Pakistan. Adult inpatients (>18 yrs) presenting to the ER who were known hypertensive and had uncontrolled hypertension were included. Results. Out of 1336 patients, 28.6% (387) had uncontrolled hyperte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
53
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(62 citation statements)
references
References 28 publications
6
53
2
1
Order By: Relevance
“…Patients with hypertensive emergencies had higher prevalence of coronary artery disease and chronic heart failure compared to uncontrolled hypertension in our population, once again in line with previous reports [ 4 , 19 ]. This finding may explain the greater use of beta-blockers, loop diuretics and acetylsalicylic acid in the former group.…”
Section: Discussionsupporting
confidence: 93%
“…Patients with hypertensive emergencies had higher prevalence of coronary artery disease and chronic heart failure compared to uncontrolled hypertension in our population, once again in line with previous reports [ 4 , 19 ]. This finding may explain the greater use of beta-blockers, loop diuretics and acetylsalicylic acid in the former group.…”
Section: Discussionsupporting
confidence: 93%
“…The main indings of this study was that the prevalence of hypertensive crisis among patients admitted to the medical emergency room at kassala teaching hospital was .81%, which is comparable to other study conducted by Carrillo et al, who reported a prevalence of HC of 0.6% among patients brought to the clinical emergency department in a Spanish university-af iliated hospital [11]. However it is inconsistent with the studies from Italy, Brazil, Bosnia and Pakistan where estimated prevalence of HC was reported as 3%,16%,47.2%and 56% respectively [1,[12][13][14]. The difference in the prevalence rate of HC between the later studies and our result may be justi ied by inclusion of hypertensive pseudocrisis which may mimic hypertensive urgency, which may alter the inal results of the study.…”
Section: Discussionmentioning
confidence: 63%
“…However, they were compatible with a much used definition for hypertensive crisis and with the findings of an international study on the clinical manifestations of patients with hypertensive crisis. ( 17 ) This data was expected, since the concept of hypertensive crisis used supports high blood pressure values. However, in the second blood pressure measurement, a reduction in blood pressure levels was observed, presuming the efficacy of the treatment conducted.…”
Section: Discussionmentioning
confidence: 68%